2011
DOI: 10.1007/s12187-011-9131-5
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Family Affluence Scale (FAS II) among Adolescents in Beijing, China

Abstract: This study comprises two sub-studies. Study I assessed the test-retest reliability of Family Affluence Scale (FAS II) items among 95 students aged 11 and 15 years old in Beijing. Study II investigated the completion rate of traditional indicators (parents' educational level, perceived family wealth, resident area, and school location) measuring socioeconomic status (SES) compared with FAS II, and examined the internal reliability, external and construct validity of the FAS II items in a population of 5876 scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 35 publications
6
78
0
3
Order By: Relevance
“…Between 2002 and 2010 the SES categories correspond to tertiles of the sum score ("low" = 0-3; "medium" = 4-6, "high" = 7-9) and in 2014 and 2018 as follows: "low" = 0-6, "medium" = 7-9, and "high" = 10-13 [18]. High validity (kappa coefficient 0.41-0.74; 76.2-88.1 agreement) and moderate reliability (Cronbach's α = 0.58) between children's and parents' responses on the FA scale-related items have been documented repeatedly [40][41][42][43][44]. Under the social and economic conditions of Czechia, the FA scale was validated with respect to the gross domestic product (Pearson correlation r = 0.773 p < .001) [45].…”
Section: Socioeconomic Statusmentioning
confidence: 94%
“…Between 2002 and 2010 the SES categories correspond to tertiles of the sum score ("low" = 0-3; "medium" = 4-6, "high" = 7-9) and in 2014 and 2018 as follows: "low" = 0-6, "medium" = 7-9, and "high" = 10-13 [18]. High validity (kappa coefficient 0.41-0.74; 76.2-88.1 agreement) and moderate reliability (Cronbach's α = 0.58) between children's and parents' responses on the FA scale-related items have been documented repeatedly [40][41][42][43][44]. Under the social and economic conditions of Czechia, the FA scale was validated with respect to the gross domestic product (Pearson correlation r = 0.773 p < .001) [45].…”
Section: Socioeconomic Statusmentioning
confidence: 94%
“…Intrapersonal factors included socio-demographics and self-efficacy. Socio-demographics included age, gender (male or female), year level (Years 7, 8 or 9), family composition (living with two parents or other living arrangement), and family affluence level (low, medium or high) [28]. Personal self-efficacy was measured by the General Self-Efficacy Scale (GSES) [29], a 10-item scale that assessed personal belief in the ability to cope with a variety of challenges in life.…”
Section: Intrapersonal Factorsmentioning
confidence: 99%
“…"; and "How many computers do your family own?" In previous research the FAS has been found to have substantial test-retest reliability (ICC = 0.88; Liu, Wang, Villberg et al, 2012), the total scores correlate significantly with the gross domestic product of a country (Boyce et al, 2006), and overall the FAS has been concluded to be a valid indicator of SES (Currie et al, 2008).…”
Section: Instrumentsmentioning
confidence: 90%
“…The Family Affluence Scale (FAS; Boyce, Torsheim, Currie & Zambon, ) is a self‐report measure of the respondents’ socioeconomic status. There are four items namely: “Does your family own a car, van, or truck?”; “Do you have a bedroom for yourself?”; “During the past 12 months, how many times did you travel away on holiday with your family?”; and “How many computers do your family own?” In previous research the FAS has been found to have substantial test‐retest reliability (ICC = 0.88; Liu, Wang, Villberg et al ., ), the total scores correlate significantly with the gross domestic product of a country (Boyce et al ., ), and overall the FAS has been concluded to be a valid indicator of SES (Currie et al ., ).…”
Section: Methodsmentioning
confidence: 97%